1999
DOI: 10.1046/j.1440-169x.1999.413428.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the adhesive properties of dissociated and reaggregated Xenopus laevis embryo cells

Abstract: Activin A is a member of the transforming growth factor ␤ superfamily, and the strongest candidate mesoderminducer. The initial adhesive property changes in amphibians are likely to be mediated by mesoderm-inducers like activin A. The manner in which these changes actually occur, however, remains poorly understood. In the present study, the adhesive property changes mediated by activin A were directly demonstrated. Activin A functioned as a morphogen at low concentrations (less than 0.5 ng/mL), with no effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We demonstrated that, when cells treated with activin A were mixed with untreated cells, the activin A-treated (1 ng/ml) cells concentrated in a central mass of the aggregates and they effectively formed notochord (Kuroda et al, 2002, Kuroda et al, 1999. Therefore, we further hypothesized that it would be possible to reproduce jaw effectively in vitro using activin A and dissociated animal cap cells and jaw induction would lead to tooth formation.…”
Section: Introductionmentioning
confidence: 94%
“…We demonstrated that, when cells treated with activin A were mixed with untreated cells, the activin A-treated (1 ng/ml) cells concentrated in a central mass of the aggregates and they effectively formed notochord (Kuroda et al, 2002, Kuroda et al, 1999. Therefore, we further hypothesized that it would be possible to reproduce jaw effectively in vitro using activin A and dissociated animal cap cells and jaw induction would lead to tooth formation.…”
Section: Introductionmentioning
confidence: 94%
“…2000). Treatment of blastula animal cap cells of Xenopus with increasing levels of activin leads to sequential differentiation of muscle, then notochord and finally endoderm (Kuroda et al . 1999).…”
Section: Number Of Cell Cycles Regulates Germ Layer Determinationmentioning
confidence: 99%
“…Total RNA was prepared from dissociated and reaggregated animal cap cells that had been treated with activin to exclusively induce notochord cells in vitro as previously shown by Kuroda et al (Asashima et al 1990;Kuroda et al 1999). The cDNA library was constructed using the SMART PCR cDNA library construction kit (Clontech Laboratories, Palo Alto, CA, USA).…”
Section: Screening and Cloningmentioning
confidence: 99%